(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Currently, many methodological innovations are associated with the use of interactive teaching methods that stimulate and develop the cognitive activity of students, their ability for independent creative, professional thinking. In this regard, of particular relevance and interest is the study of the possibility of using interactive teaching methods and techniques in the educational process at school. The active introduction of interactive methods and techniques in the process of teaching chemistry helps to increase the efficiency of the educational process, since almost all children are actively involved in the learning process.